2004
DOI: 10.1159/000077523
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptors in the Developing Brain and Effects of Noxious Insults

Abstract: This review covers normal expression of the NMDA receptor in the fetus and newborn, and then the response of the NMDA receptors within the central nervous system (CNS) during early development, to noxious stimuli. In the research setting, hypoxia is a commonly studied noxious stimulus that has been studied in a variety of contexts, including isolated hypoxia, or hypoxia combined with ischemia or hypercapnia, and delivered in single or repeated doses (intermittent stimuli). We review differences and commonaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 121 publications
1
17
0
1
Order By: Relevance
“…IHH is a potent pathological noxious insult that induces unique pathophysiological effects on neurons of the brain (Waters and Machaalani, 2004). It is plausible that exposure to hypoxia reduces production/synthesis of orexin at the mRNA level which subsequently manifests at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…IHH is a potent pathological noxious insult that induces unique pathophysiological effects on neurons of the brain (Waters and Machaalani, 2004). It is plausible that exposure to hypoxia reduces production/synthesis of orexin at the mRNA level which subsequently manifests at the protein level.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increase in hypernociceptive behavior, downregulation of expression of the NR1 subunit occurred in the magnesium-deficiency group treated with Cg. This may reflect a necessary adaptive response to avoid excessive neuronal excitability, glutamate-induced NMDA-R overstimulation, and an excitotoxic process that leads to cell death, all of which can be observed in many neurological conditions (36)(37)(38)(39). However, we did not observe a decrease in phospho-NR1; rather, we observed an increase of phospho-NR1 in the magnesium-depleted Cg group in comparison with the Cg group.…”
Section: Discussionmentioning
confidence: 99%
“…Since NMDARs play an important role on neural cell growth and differentiation in hippocampus, expression of NMDARs in hippocampus has been implicated as important indicators of both learning and neural development [39]. Several studies indicated that there is NMDAR 1A/2B subunits combination in immature brain and NMDAR 1A/2A subunits combination in mature brain [40,41].…”
Section: Discussionmentioning
confidence: 99%